Characterization of the Potential Role of NTPCR in Epithelial Ovarian Cancer by Integrating Transcriptomic and Metabolomic Analysis - Shang, Hongkai; Zhang, Huizhi; Ren, Ziyao; Zhao, Hongjiang; Zhang, Zhifen; Tong, Jinyi (Frontiers in Genetics, 2021)
Background: Epithelial ovarian carcinoma (EOC) is a malignant tumor with high motility in women. Our previous study found that dysregulated NTPCR was associated with the prognosis of ovarian cancer patients, and thus this present study attempted to explore the potential roles of nucleoside-triphosphatase cancer-related (NTPCR) in disease progression. Methods: Expressed level of NTPCR was investigated in ovarian cancer cell lines by RT-qPCR analysis. shRNA targeting NTPCR was generated and transfected into SKOV3 cells to detect the effect of knocking out NTPCR on cell proliferation, cell cycle, cell migration, and invasion. Transcriptomic sequencing and metabolite profiling analysis were performed in shNTPCR groups to identify transcriptome or metabolites alteration that might contribute to ovarian cancer. And finally, we searched the overlapped signaling pathways correlated with differential metabolites and DEGs by integrating analysis. Results: NTPCR was upregulated in EOC cell lines compared with human ovarian epithelium cell IOSE80, especially in SKOV3 and OVCAR-3 (SKOV3 vs IOSE80, P<0.001; OVCAR-3 vs IOSE80, P<0.001). Knocking out NTPCR can induce cell proliferation and S phase arrest, promote migration and invasion in SKOV3 cells. RNA sequencing analysis demonstrated cohorts of differential expressed genes (DEGs) were identified in shNTPCR samples. PPI networks were constructed for DEGs. STAT1 (degree = 43) and OAS2 (degree = 36) were identified as hub genes in network. Several miRNAs together with target genes were predicted to be crucial genes related to disease progression, including hsa-miR-124-3p, hsa-miR-30a-5p, hsa-miR-146a-5, EP300, GATA2, and STAT3. We also screened the differential metabolites from shNTPCR samples, including 22 upregulated and 22 downregulated metabolites. By integrating analysis, eight overlapped pathways were correlated with these DEGs and differential metabolites, such as primary bile acid biosynthesis, protein digestion, and absorption, pentose and glucuronate interconversions. Conclusion: NTPCR might serve as a tumor suppressor in EOC progression. Our results demonstrated that DEGs and differential metabolites were mainly related to several signaling pathways, which might be a crucial role in the progression of ovarian cancer.